Method for preparing phenolic chemicals by using cobalt-based nitrogen-carbon composite material to catalyze lignin transfer hydrogenolysis
By using cobalt-based nitrogen-carbon composite catalysts to perform hydrogen transfer catalysis without external hydrogenation, the high cost and high risk problems in the existing lignin hydrogenolysis process are solved, and efficient conversion of lignin and monophenolic products are achieved. High yield and improved catalyst stability and recyclability.
Patent Information
- Application Number
- CN202411322524.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-23
AI Technical Summary
The existing hydrogenolysis process of lignin relies on external hydrogen gas, resulting in high equipment and energy costs, and the risk of high temperature and high pressure. The traditional catalyst has poor stability and poor recycling.
The cobalt -based nitrogen carbon composite material is used as a catalyst, and the hydrogen hydrogen is catalyzed by hydrogenation through hydrogen to the hydrogenation. Organic solvents are used as a hydrogen supply body to reduce the reaction temperature and pressure, and improve the stability and activity of the catalyst.
The efficient conversion of lignin and the high revenue of single -phenol products, the conversion rate reached 74.4 to 91.3%, the total revenue of single phenol products reached 7.8 to 17.7%, the selectivity was 38.4 to 50.8%, and the catalyst was circulating in the cycle. After 5 times, the activity did not significantly decrease.
Smart Images

Figure CN119350131A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to catalytic hydrogenolysis of bagasse lignin, and in particular to a method for preparing high-value-added phenolic chemicals by catalyzing transfer hydrogenolysis of lignin using a cobalt-based nitrogen-carbon composite material, and belongs to the field of high-value utilization of renewable biomass. Background Art
[0002] Traditional fossil fuels such as oil, coal and natural gas are still the main energy sources to maintain industrial operation. The large-scale development and utilization of these non-renewable resources has brought about energy crises and exacerbated environmental problems such as global warming. In this context, China is actively advocating the energy transformation strategies of "carbon neutrality" and "carbon peak", and constantly exploring and developing renewable energy and clean energy. In the process of exploring new energy, biomass energy has become an ideal alternative to fossil fuels with its wide distribution, abundant reserves, low pollution and renewable characteristics. Therefore, its efficient utilization is of great significance to promoting energy transformation.
[0003] Lignin is a highly polymerized and amorphous three-dimensional network macromolecule rich in aromatic structures. It is composed of different methoxylated phenylpropane structural units connected by different CO bonds and CC bonds. In addition to structural units and CO, CC, lignin also contains various functional groups, which is an excellent raw material for the production of high value-added products such as aromatic hydrocarbons and phenolic chemicals. However, due to its internal cross-linked structure and complex and disordered chemical bonds, the depolymerization products of lignin are complex. Therefore, the current industrial application of lignin is very limited, and 95% of industrial lignin is directly burned as fuel.
[0004] At present, most lignin hydrogenolysis processes rely on external hydrogen as a hydrogen source for upgrading lignin and its derivatives, which increases equipment and energy costs. At the same time, the reaction process involving hydrogen is very risky under high temperature and high pressure conditions. Industrial hydrogen mainly comes from the reforming of fossil resources. The process of depolymerizing lignin under external hydrogen is not green enough and has high cost. Therefore, catalytic transfer hydrogenolysis (CTH) is an effective alternative method to avoid the use of high-pressure H2 to crack the aromatic ether bonds of lignin.
[0005] Catalytic transfer hydrogenolysis is a catalytic hydrogenation reaction in the presence of a metal catalyst, using organic compounds instead of hydrogen as the hydrogen donor in the reaction. Cheap alcohols (methanol, ethanol, isopropanol, etc.) are usually used as hydrogen donor solvents. On the one hand, the CH bond in the alcohol is easier to break than the HH in the H2 molecule, and the H atom formed in situ is more active than the gaseous H2 molecule; on the other hand, the use of hydrogen donor organic solvents avoids the problem of difficult dissolution of H2 molecules, thereby reducing the gas-liquid mass transfer resistance. Precious metals such as Re and Ru are widely used in the catalytic hydrogenation reaction of lignin, showing excellent catalytic performance. However, their high cost limits their further application. In recent years, low-cost, high-performance non-precious metal catalysts have attracted widespread attention. For example, Ni, Cu and Co-based catalysts have shown high activity similar to that of precious metal-based catalysts.
[0006] Chinese invention patent application CN202410215194.0 discloses a method for preparing C2-phenol monomers by hydrogenolysis of lignin using a nickel-based alkaline supported catalyst. The method uses a nickel-based alkaline supported catalyst, lignin as a substrate, isopropanol as a hydrogen source, and reacts at 200-330°C for 1-6 hours to obtain C2-phenol monomer products (4-ethylphenol and 4-ethylguaiacol), with a selectivity of up to 58.2%. However, the alkaline supported catalyst used in this technology is easily deactivated during the reaction, and the cyclic stability needs to be further enhanced.
[0007] Chinese invention patent application CN202311659296.3 discloses a method for preparing phenolic compounds by depolymerizing lignin with a RuNiZn / Nb2O5 catalyst. The method uses natural biomass raw materials as substrates, reacts at 200-280°C and a hydrogen pressure of 1-3MPa for 0.5-6h to obtain C6-C9 aromatic hydrocarbons. The RuNiZn / Nb2O5 catalyst used in this method can improve the reaction activity of the catalyst and reduce the use of precious metals. However, in this technology, the addition of exogenous hydrogen increases the equipment cost and energy cost, and industrial hydrogen mainly comes from the reforming of fossil resources. Therefore, this technical route does not meet the requirements of green chemistry, and the cost is still relatively high.
[0008] Chinese invention patent application CN202410599907.8 discloses a method for the efficient hydrogenolysis of aromatic ethers using a boron nitride-supported ruthenium catalyst, in which ruthenium metal is loaded onto commercial nano-boron nitride by ball milling and in-situ reduction to prepare a boron nitride-supported ruthenium catalyst. The method uses lignin-type compounds as substrates, including benzyl phenyl ether, diphenyl ether, 4,4-dihydroxydiphenyl ether, phenoxyethylbenzene and 4-benzyloxyphenol, and reacts at 150-180°C for 6-10h under an inert gas atmosphere of 1-2MPa. The product has high selectivity and can efficiently catalyze the hydrogenolysis of aromatic ether bonds in lignin model compounds. However, the precious metal catalysts used in this technology have small reserves and high costs; and compared with lignin derivatives, the structure of real lignin is more complex and stable, so the depolymerization value of this technology for real lignin is limited. Summary of the invention
[0009] In order to overcome the shortcomings of the prior art, the present invention aims to provide a multi-level porous nitrogen-carbon composite material catalyst with high stability and catalytic activity, a method for preparing aromatic compounds by catalyzing the hydrogenolysis of lignin through a hydrogen transfer pathway, using real lignin as a reaction substrate, and realizing the lignin conversion process without the addition of external hydrogen by constructing an efficient catalytic system, thereby effectively reducing hydrogen energy consumption; after the reaction, the lignin conversion rate reaches 74.4-91.3%, and the total yield of monophenol products reaches 7.8-17.7%, among which the para-hydroxyphenyl products can reach 4.2-9.0%, and the selectivity is 38.4-50.8%.
[0010] The purpose of the present invention is achieved through the following technical solutions:
[0011] A method for preparing phenolic chemicals by catalyzing lignin transfer hydrogenolysis using a cobalt-based nitrogen-carbon composite material, comprising: using organic soluble lignin as a raw material, using a cobalt-based nitrogen-carbon composite material as a catalyst, using an organic small molecule alcohol and formic acid as a mixed solvent and a hydrogen supply reagent, reacting at 210-250° C. for 2-6 hours in an inert gas atmosphere of 0.5-3 MPa, catalyzing the depolymerization of lignin to obtain a monophenol product mainly composed of 4-ethylphenol; the cobalt-based nitrogen-carbon composite material is obtained by heat-treating a Co-NDC precursor at 400-700° C. in a reducing atmosphere; the Co-NDC precursor is obtained by refluxing cobalt nitrate hexahydrate, 2,6-naphthalene dicarboxylic acid and 1,10-phenanthroline in a mixed solution at 100-120° C., filtering, drying and grinding; the mixed solution consists of N,N-dimethylformamide (DMF), water and an alkaline regulator.
[0012] To further achieve the purpose of the present invention, preferably, the molar ratio of the cobalt nitrate hexahydrate, 2,6-naphthalene dicarboxylic acid and 1,10-phenanthroline is (0.5-1.5):1:1; the mass ratio of the cobalt nitrate hexahydrate and the mixed solution is 1:(90-110); the volume ratio of N,N-dimethylformamide, water and alkaline regulator in the mixed solution is 20:1:(1.5-2.5).
[0013] To further achieve the purpose of the present invention, preferably, the reflux time at 100-120° C. is 24-32 hours; the alkaline regulator is one or more of formamide, diethylamine, N,N-tetramethylhexanediamine, and isopropanolamine.
[0014] Preferably, the mass ratio of the organic soluble lignin to the cobalt-based nitrogen-carbon composite material is 1:(0.5-1.5); the mass ratio of the organic small molecule alcohol to formic acid in the mixed solvent is 9:(0.5-1.5); and the mass ratio of the organic soluble lignin to the mixed solvent is 1:(7-9).
[0015] Preferably, the reducing atmosphere is a carbon monoxide / nitrogen mixture; the inert gas atmosphere is any one or more of nitrogen, argon and helium; and the catalytic lignin depolymerization is carried out in an intermittent high-pressure reactor.
[0016] Preferably, the heat treatment time is 6 to 7 hours; the organic small molecule alcohol is any one or more of methanol, ethanol, n-propanol, isopropanol and formic acid.
[0017] Preferably, the organosoluble lignin is obtained by extracting biomass as a substrate through an organic solvent method.
[0018] Preferably, the organic solvent extraction is to react the biomass with a mixed extract of 1,4-dioxane / dilute sulfuric acid at 90-150° C. for 2-8 hours, filter the filtrate, add deionized water to the filtrate to precipitate lignin, let it stand for 12-24 hours, then filter, dry and grind the filter cake to obtain the organic soluble lignin;
[0019] Preferably, the biomass is any one or more of bagasse, corn stalks, corn cobs, bamboo, poplar, birch and pine, which is obtained by mechanical crushing and sieving to 80-120 mesh; in the 1,4-dioxane / dilute sulfuric acid extract, the volume ratio of 1,4-dioxane to dilute sulfuric acid is (6-7):1; the amount of ethanol / water mixed extract per gram of biomass raw material is 10-20 mL; the dilute sulfuric acid is prepared by adding 9-12 g of deionized water to concentrated sulfuric acid with a mass concentration of 95-98% per gram.
[0020] Preferably, the monophenols include 4-ethylphenol, 4-propylphenol, p-hydroxyphenylpropionic acid, 4-ethylguaiacol, 4-propylguaiacol, 4-propyleneguaiacol, 2,6-dimethoxyphenol, 2,6-dimethoxy-4-propylphenol, and 2,6-dimethoxy-4-propylenephenol.
[0021] Compared with the existing lignin catalytic transfer hydrogenolysis technology, the technical solution of the present invention has the following advantages:
[0022] (1) The present invention is based on the current problems of low lignin depolymerization conversion rate and low product yield. On the one hand, by enhancing the electronic interaction between the metal and the carrier, the catalyst can significantly promote the efficient hydrogen evolution of the hydrogen supply solvent while catalyzing the efficient depolymerization of lignin, thereby avoiding the high temperature and high pressure reaction process of traditional hydrogenolysis under external hydrogen supply conditions, and realizing the green and safe conversion of lignin under mild conditions; on the other hand, by the reasonable selection of the reaction medium and the catalyst, the synergistic coordination of the reaction medium and the catalyst can be achieved. The reaction medium can not only promote the dissolution of the substrate and thus increase the contact area between the substrate and the catalyst, but also further promote the exposure of the catalyst active sites and the progress of the hydrogenolysis reaction due to its physicochemical properties (such as solubility, polarity, ionic strength, etc.), forming a virtuous cycle of "medium promoting catalysis, catalysis increasing medium efficiency", thereby promoting the hydrogenolysis of lignin, so that the conversion rate of lignin reaches 74.4-91.3%, the total yield of monophenol products reaches 7.8-17.7%, among which the p-hydroxyphenyl products can reach 3.2-9.0%, and the selectivity is 21.3-50.8%.
[0023] (2) The catalyst used in the present invention adds formamide as an alkaline regulator during the preparation process to regulate the deprotonation process of 2,6-naphthalene dicarboxylic acid, thereby regulating the growth rate of the crystal, and obtaining a multi-level porous material that is mainly mesoporous and contains a small amount of micropores. This pore structure is beneficial to the mass transfer of lignin macromolecules, thereby improving its reaction activity.
[0024] (3) The cobalt-based nitrogen-carbon material catalyst used in the present invention has excellent catalytic activity. On the one hand, nitrogen doping enhances the electronic interaction between the active metal and the carrier, enhances the stability of the active metal in the carrier, prevents its leaching and anchors the metal site, and increases the dispersion of the metal species on the carrier; on the other hand, it can change the electronic structure of the metal center and redistribute the charge density, thereby improving the catalytic activity of the catalyst. At the same time, it adjusts the overall acidity and alkalinity of the catalyst so that it has a suitable acid-base site to further enhance the catalytic activity. Compared with the cobalt-based carbon material catalyst without nitrogen doping, the monophenol yield of lignin depolymerization catalyzed by the nitrogen-doped catalyst was increased from 12.3% to 16.2%.
[0025] (4) The catalyst preparation process used in the present invention is simple and has little environmental pollution. The reaction conditions for lignin depolymerization are mild, and a high monophenol yield can be obtained at a reaction pressure of 1 to 3 MPa and a reaction temperature of 210 to 250° C., which is beneficial to reducing energy consumption and achieving lignin depolymerization under mild conditions.
[0026] (5) The catalyst of the present invention has strong stability and its activity does not decrease significantly after being recycled for 5 times, which is significantly better than existing similar catalysts.
[0027] (6) The cobalt-based nitrogen-carbon material catalyst used in the present invention is mainly a mesoporous catalyst, and there are also a small amount of micropores and macropores, showing a block support structure of sheet stacking, which is beneficial to the mass transfer of lignin macromolecules inside the catalyst and reduces the mass transfer resistance, and can also provide abundant active sites for chemical reactions, thereby promoting the hydrogen production and hydrogenolysis reactions. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The XRD patterns of the different catalysts 1 to 4 in Example 1 of the present invention are shown in FIG.
[0029] Figure 2 This is the N2 physical adsorption-desorption isotherm of the Co@NC-500 catalyst in Example 1 of the present invention.
[0030] Figure 3 This is the pore size distribution diagram of the Co@NC-500 catalyst in Example 1 of the present invention.
[0031] Figure 4 This is the SEM image of the Co@NC-500 catalyst in Example 1 of the present invention.
[0032] Figure 5 This is the Co 2p spectrum in the XPS spectrum of the Co@NC-500 catalyst in Example 1 of the present invention.
[0033] Figure 6 This is the N1s spectrum in the XPS spectrum of the Co@NC-500 catalyst in Example 1 of the present invention.
[0034] Figure 7 This is a gas chromatography-flame ionization detector (GC-FID) graph of the volatile products obtained by catalytic transfer hydrogenolysis of lignin catalyzed by catalytic Co@NC-500 in Example 18 of the present invention.
[0035] Figure 8 This is a mass spectrum (MS) of the main product 4-ethylphenol obtained by catalytic depolymerization of organosoluble bagasse lignin in Example 18 of the present invention. DETAILED DESCRIPTION
[0036] In order to better understand the present invention, the present invention is further described below in conjunction with the accompanying drawings and embodiments, but the embodiments of the present invention are not limited thereto.
[0037] The catalytic depolymerization of lignin of the present invention is carried out by filling an intermittent high-pressure reactor with inert gas, and using an organic solvent instead of hydrogen as a hydrogen donor to improve the reducing atmosphere. Specifically, the present invention is a method for preparing phenolic chemicals by catalytic transfer hydrogenolysis of lignin using a cobalt-based nitrogen-carbon composite material: using organic soluble lignin as a raw material, a cobalt-based nitrogen-carbon composite material as a catalyst, and organic small molecule alcohol and formic acid as a mixed solvent; the mixed solvent is also a hydrogen donor, and reacts for 2 to 6 hours at a temperature of 210 to 250°C under an inert gas atmosphere of 0.5 to 3 MPa to catalyze the depolymerization of lignin to obtain a monophenol product mainly composed of 4-ethylphenol; the cobalt-based nitrogen-carbon composite material (Co@NC) catalyst is derived from a metal organic framework precursor synthesized by coordination of transition metal cobalt with 2,6-naphthalene dicarboxylic acid and 1,10-phenanthroline. In the preparation of the catalyst, a Co-NDC precursor is first synthesized, and then the Co-NDC precursor is heat-treated under different reducing atmospheres (carbon monoxide / nitrogen mixed gas);
[0038] (1) Synthesis of Co-NDC precursor: Cobalt nitrate hexahydrate, 2,6-naphthalene dicarboxylic acid and 1,10-phenanthroline are used as raw materials, N,N-dimethylformamide (DMF) is used as solvent, formamide is used as alkaline regulator, reflux stirring at 100-120°C, aged, filtered and dried to obtain Co-NDC precursor;
[0039] (2) Reduction of Co-NDC precursor: First, the Co-NDC precursor is placed in a reduction furnace and heat treated (400-700°C) in a reducing atmosphere (carbon monoxide / nitrogen mixture) for a period of time (preferably 6-7 hours) to obtain a cobalt-based nitrogen-carbon composite material (Co@NC) catalyst.
[0040] Among them, Co-NDC is used as a catalyst precursor to provide Co, O, N, C, and H elements for the catalyst. Co-NDC is called a catalyst precursor because after the reduction treatment, the structure and morphology of the Co-NDC precursor are basically completely changed, forming a cobalt-based nitrogen-carbon composite material (Co@NC) catalyst with Co and Co3O4 as active centers and nitrogen-doped carbon (NC) as a carrier. The single substance Co in the catalyst has the activity of catalyzing lignin hydrogenolysis and catalytic hydrogen transfer, and Co3O4 has the activity of hydrogenation and deoxygenation, which can perform one-step hydrogenation and deoxygenation of lignin, that is, the depolymerization of lignin and partial hydrogenation and deoxygenation of the depolymerization product are achieved in the same reaction process. The steps are simple and suitable for intermittent and continuous production. The catalyst of the present invention can realize the catalytic transfer hydrogenolysis of lignin to prepare monophenolic compounds without the addition of external hydrogen. The outstanding feature is that the reaction conditions are mild. Compared with the high pressure hydrogen and high reaction temperature (250-500°C, above 250°C, the reaction effect at 250°C is very poor) required for the traditional hydrogenolysis of lignin, the present invention uses organic solvents to supply hydrogen and endogenous hydrogen from lignin to realize the conversion of lignin without the addition of external hydrogen. The catalytic hydrogen transfer and hydrogenation deoxygenation process effectively reduce the hydrogen consumption and improve the safety and controllability of the reaction process. In particular, the reaction temperature is further reduced, and the hydrogenolysis of lignin can be realized under mild conditions of 210-250°C to obtain monophenolic compounds. The present invention can also regulate the distribution of target products by regulating the calcination temperature of the catalyst.
[0041] Preferably, the small molecule organic solvent can be any one or two of methanol, ethanol, isopropanol, n-hexanol and formic acid; the lignin can be derived from any one of bagasse, corn stalks, poplar and bamboo; the mass ratio of lignin to nickel-based catalyst is 1:0.5 to 1:1.5; the mass ratio of lignin to alcohol solvent is 1:9 to 1:10.
[0042] The monophenol product of the present invention is one or more of 4-ethylphenol, 4-propylphenol, p-hydroxyphenylpropionic acid, 4-ethylguaiacol, 4-propylguaiacol, 4-propyleneguaiacol, 2,6-dimethoxyphenol, 2,6-dimethoxy-4-propylphenol and 2,6-dimethoxy-4-propylenephenol.
[0043] Example 1: Preparation of cobalt-based nitrogen-carbon composite catalyst Co@NC-400
[0044] The preparation of the cobalt-based nitrogen-carbon composite catalyst Co@NC-400 includes the following two steps:
[0045] (1) Preparation of cobalt-based metal-organic framework Co-NDC precursor: 1.545 g of 99% pure cobalt nitrate hexahydrate, 1.264 g of 99% pure 2,6-naphthalene dicarboxylic acid, and 0.640 g of 99% pure 1,10-phenanthroline were dissolved in 20 mL of deionized water, 200 mL of DMF, and 20 mL of formamide mixed solvent, stirred evenly at room temperature, and then placed in an oil bath and heated to reflux at 120°C for 32 h. The Co-NDC precursor was filtered, washed, dried, and ground.
[0046] (2) Preparation of cobalt-based nitrogen-carbon composite catalyst Co@NC-400: The Co-NDC precursor obtained in (1) was placed in a 80 mL min -1 In a nitrogen atmosphere, the -1 Heated to 200℃ at a rate of 1.5℃·min, maintained for 2h, and then heated at 5℃·min -1 The catalyst was heated to 400 °C at a rate of 1.5 °C and maintained for 2 h to obtain Co@NC-400 catalyst.
[0047] Example 2: Preparation of oxygen-containing cobalt-based nitrogen-carbon composite catalyst Co@NC-500
[0048] The preparation of the cobalt-based nitrogen-carbon composite catalyst Co@NC-500 also includes two steps:
[0049] (1) Preparation of cobalt-based metal-organic framework Co-NDC precursor: 1.545 of cobalt nitrate hexahydrate with a purity of 99%, 1.264 of 2,6-naphthalene dicarboxylic acid with a purity of 99%, and 0.640 of 1,10-phenanthroline with a purity of 99% were dissolved in a mixed solvent of 20 mL of deionized water, 200 mL of DMF, and 20 mL of formamide, stirred evenly at room temperature, and then placed in an oil bath and heated to reflux at 120°C for 32 h. The Co-NDC precursor was filtered, washed, dried, and ground.
[0050] (2) Preparation of cobalt-based nitrogen-carbon composite catalyst Co@NC-500: The Co-NDC precursor obtained in (1) was placed in a 80 mL min -1 In a nitrogen atmosphere, the -1 Heated to 200℃ at a rate of 1.5℃·min, maintained for 2h, and then heated at 5℃·min -1 The catalyst was heated to 500 °C at a rate of 1.54 °C and maintained for 2 h to obtain Co@NC-500 catalyst.
[0051] Example 3: Preparation of oxygen-containing cobalt-based nitrogen-carbon composite catalyst Co@NC-600
[0052] The preparation of the cobalt-based nitrogen-carbon composite catalyst Co@NC-600 also includes two steps:
[0053] (1) Preparation of cobalt-based metal-organic framework Co-NDC precursor: 1.545 g of 99% pure cobalt nitrate hexahydrate, 1.264 g of 99% pure 2,6-naphthalene dicarboxylic acid, and 0.640 g of 99% pure 1,10-phenanthroline were dissolved in 20 mL of deionized water, 200 mL of DMF, and 20 mL of formamide mixed solvent, stirred evenly at room temperature, and then placed in an oil bath and heated to reflux at 120°C for 32 h. The Co-NDC precursor was filtered, washed, dried, and ground.
[0054] (2) Preparation of cobalt-based nitrogen-carbon composite catalyst Co@NC-600: The Co-NDC precursor obtained in (1) was placed in a 80 mL min -1 In a nitrogen atmosphere, the -1 Heated to 200℃ at a rate of 1.5℃·min, maintained for 2h, and then heated at 5℃·min -1 The catalyst was heated to 600 °C at a rate of 1.5 °C and maintained for 2 h to obtain Co@NC-600 catalyst.
[0055] Example 4: Preparation of oxygen-containing cobalt-based nitrogen-carbon composite catalyst Co@NC-700
[0056] The preparation of the cobalt-based nitrogen-carbon composite catalyst Co@NC-700 also includes two steps:
[0057] (1) Preparation of cobalt-based metal-organic framework Co-NDC precursor: 1.545 g of 99% pure cobalt nitrate hexahydrate, 1.264 g of 99% pure 2,6-naphthalene dicarboxylic acid, and 0.640 g of 99% pure 1,10-phenanthroline were dissolved in 20 mL of deionized water, 200 mL of DMF, and 20 mL of formamide mixed solvent, stirred evenly at room temperature, and then placed in an oil bath and heated to reflux at 120°C for 32 h. The Co-NDC precursor was filtered, washed, dried, and ground.
[0058] (2) Preparation of cobalt-based nitrogen-carbon composite catalyst Co@NC-700: The Co-NDC precursor obtained in (1) was placed in a 80 mL min -1 In a nitrogen atmosphere, the -1 Heated to 200℃ at a rate of 1.5℃·min, maintained for 2h, and then heated at 5℃·min -1 The catalyst was heated to 700 °C at a rate of 1.5 °C and maintained for 2 h to obtain Co@NC-700 catalyst.
[0059] Figure 1The XRD patterns of the catalysts prepared at different reduction temperatures in Examples 1 to 4 show that when the reduction temperature is higher than 500°C, the series of catalysts can all observe the single substance Co (PDF#15-0806) crystal phase belonging to the face-centered cubic structure (FCC), wherein the diffraction peak at 2θ=44.2° corresponds to the (111) crystal plane of the metal single substance Co. As the reduction temperature increases, the diffraction peak intensity of Co increases.
[0060] The prepared Co@NC-500 catalyst was characterized by N2 physical adsorption and desorption to explore its pore structure. Figure 2 and Figure 3 As shown. Figure 2 It can be seen that the adsorption isotherm of Co@NC-500 is a typical type IV isotherm, and an obvious H4 type hysteresis loop can be observed in the medium relative pressure range (P / P0=0.4~1.0), indicating that the carrier has a mesoporous structure. Figure 3 From the pore size distribution diagram, it can be seen that the main pore structure of the carrier is mesopores of 12 to 50 nm, and contains a small amount of micropores of 1 to 2 nm and macropores of 50 to 100 nm.
[0061] The prepared Co@NC-500 catalyst was characterized by SEM to explore its surface morphology. Figure 4 It can be clearly observed that the morphology of the carrier is stacked sheets with spherical clusters distributed on the surface.
[0062] XPS characterization of the prepared Co@NC-500 catalyst was performed to explore the existence forms of Co and N elements on its surface. Figure 5 and 6 shown. Figure 5 The Co 2p spectrum of Co@NC-500 catalyst. The Co element in the catalyst is represented by Co 3+ 、Co 2+ 、Co 0 There are three forms, accounting for 43.9%, 36.6% and 19.5% respectively. The two characteristic peaks at 778.8eV and 794.4eV correspond to Co 0 2p 3 / 2 and Co 0 2p 1 / 2 orbital, the characteristic peaks at 782.3eV and 798.0eV are respectively attributed to Co 2 + 2p 3 / 2 and Co 2+ 2p 1 / 2 orbital, the characteristic peaks at 780.5eV and 796.2eV are respectively attributed to Co 3+ 2p 3 / 2 and Co3+ 2p 1 / 2 Compared with the standard characteristic peaks, their binding energies are all shifted to higher positions, indicating that there is electron transfer between Co and the support, which further proves the interaction between the metal and the support. Most of the Co species on the Co@NC-500 catalyst exist in the form of metal oxides, while the unique CoO species with suitable oxygen vacancies can strongly adsorb lignin macromolecules and catalyze the homolytic / heterolytic cleavage of H2 molecules to produce highly active H δ- Species. Figure 6 This is the N 1s spectrum of the Co@NC-500 catalyst. The N element in the catalyst exists in three forms: pyridine N, Co-N, and nitrogen oxides, accounting for 72.7%, 19.6%, and 7.7%, respectively. The pyridine N and Co-N bonds can stabilize the cobalt nanoparticles. The bonding between Co and N indicates that the catalyst has obvious metal-support interaction forces, which can prevent the agglomeration of cobalt nanoparticles during pyrolysis and improve the dispersion of Co.
[0063] Example 5: Preparation of monophenolic compounds by transfer hydrogenolysis of bagasse lignin catalyzed by Co@NC-500
[0064] (1) Extraction of lignin: The bagasse is mechanically crushed and sieved, and the 80-120 mesh bagasse powder is sealed and stored for later use. The mass ratio of 1,4-dioxane / dilute sulfuric acid (1M) in the extract is 20:3. 20g bagasse powder and 230mL extract are placed in a hydrothermal reactor and heated at 90°C for 2h. After the reaction is completed, it is naturally cooled to room temperature. Filter, take the liquid phase, add 500mL deionized water, and let it stand to allow lignin to precipitate. Filter again, take the solid phase, vacuum dry overnight, grind and store in the dark. The resulting lignin is defined as organic-soluble bagasse lignin.
[0065] (2) Catalytic transfer hydrogenolysis of lignin: The catalytic hydrogenolysis of lignin was carried out in a high-pressure reactor. Weigh 50 mg of Co@NC-500 catalyst, 100 mg of bagasse lignin, 9 mL of isopropanol and 1 mL of formic acid and mix them in a reactor. The reactor was sealed. After replacing the air in the reactor with argon for 5 times, 1 MPa of argon was filled in. A thermocouple was connected. The reactor was heated at 5 °C min at a speed of 600 rpm. -1 Heat to 230°C at a rate of 1000 ℃ and hold for 4 h.
[0066] Collect the gaseous products after the reaction and perform qualitative and quantitative analysis on them by gas chromatography (GC-TCD). Filter the solid-liquid mixture in the reactor and wash the filter cake with the reaction solvent several times. The filter cake is the catalyst and the solid product after the reaction. The liquid product after the reaction includes the reaction solvent and the lignin hydrogenolysis product generated by the reaction. Transfer the liquid product and the above-mentioned washing liquid to a 25mL volumetric flask, add the internal standard dimethyl phthalate, and make up the volume with the reaction solvent to achieve the purpose of diluting the liquid product. Pipette 1.5mL of the test solution into the injection bottle and detect it by gas chromatography-mass spectrometry (GC-MS). Heating program: maintain at 50℃ for 1min, and increase the temperature at 10℃·min -1 The temperature was raised to 250°C at a rate of 100°C and maintained for 31 minutes to quantitatively analyze the liquid products in the reaction. An appropriate amount of deionized water was added to the reaction solution, and the solution was allowed to stand for a long time to precipitate the regenerated lignin, which was then filtered and dried to a constant weight to obtain the regenerated lignin.
[0067] The distribution and yield of liquid volatile products can be obtained by GC-MS detection, and then the conversion rate of organic soluble lignin (Conversion) and the total yield of volatile products (Yield) can be calculated. The calculation formulas are shown in (1) to (2):
[0068]
[0069] Among them, m0 is the original lignin mass (g), m R is the mass of regenerated lignin after reaction (g), m v is the mass of volatile products (g).
[0070] Figure 8 The mass spectrum (MS) of the main product 4-ethylphenol obtained by catalyzing the depolymerization of organosoluble bagasse lignin in this embodiment. In mass spectrometry, the maximum mass-to-charge ratio (m / z) usually corresponds to the relative molecular mass of a molecule. As shown in the figure, the maximum mass-to-charge ratio (m / z) of the product is 122, corresponding to the relative molecular mass (122) of 4-ethylphenol. At the same time, by comparing the AgilentNIST MS Search 2.4 database, it is determined that the product is 4-ethylphenol.
[0071] Comparison Figure 7 Table 1 shows the retention time and yield of different volatile products. As can be seen from the table, the yields of 4-ethylphenol, 4-propylguaiacol, 4-propylsyringol, and p-hydroxyphenylpropionic acid in the product are relatively high, reaching 6.1%, 2.4%, 3.8%, and 2.8%, respectively, and the total yield of monophenol compounds is 17.7%.
[0072] Table 1 Product distribution and yield of phenolic compounds prepared by catalytic transfer hydrogenolysis of lignin
[0073]
[0074]
[0075] The gas chromatography-flame ionization detector (GC-FID) graph of the volatile products obtained by catalytic transfer hydrogenolysis of lignin in the following examples and the mass spectrum (MS) graph of the main product 4-ethylphenol obtained by catalytic depolymerization of organosoluble bagasse lignin are basically similar to those in Example 5 and are not provided one by one.
[0076] Example 6: Preparation of monophenolic compounds by transfer hydrogenolysis of bagasse lignin catalyzed by Co@NC-400
[0077] The difference between this embodiment and embodiment 5 is that:
[0078] Weigh 50 mg Co@NC-400 catalyst, 100 mg bagasse lignin, 9 mL isopropanol and 0.5-1.5 mL formic acid, mix and place in a reactor, and seal the reactor. Replace the air in the reactor with argon for 5 times, and then fill it with 1 MPa argon. Connect the thermocouple. At a speed of 600 rpm, heat the reactor at 5 °C min. -1 Heat to 230°C at a rate of 1000 ℃ and hold for 4 h.
[0079] In this example, the lignin conversion rate was 74.4%, the total yield of monophenol products was 7.8 wt.%, the yield of 4-ethylphenol was 3.2 wt.%, and the selectivity was 41.0%.
[0080] Example 7: Preparation of monophenolic compounds by transfer hydrogenolysis of bagasse lignin catalyzed by Co@NC-600
[0081] The difference between this embodiment and embodiment 5 is that:
[0082] Weigh 50 mg Co@NC-600 catalyst, 100 mg bagasse lignin, 9 mL isopropanol and 1 mL formic acid, mix and place in a reactor, and seal the reactor. Replace the air in the reactor with argon for 5 times, and then fill it with 1 MPa argon. Connect the thermocouple. At a speed of 600 rpm, heat the reactor at 5 °C min. -1 Heat to 230°C at a rate of 1000 ℃ and hold for 4 h.
[0083] In this example, the lignin conversion rate was 83.9%, the total yield of monophenol products was 13.8 wt.%, the yield of 4-ethylphenol was 4.2 wt.%, and the selectivity was 30.4%.
[0084] Example 8: Preparation of monophenolic compounds by transfer hydrogenolysis of bagasse lignin catalyzed by Co@NC-700
[0085] The difference between this embodiment and embodiment 5 is that:
[0086] Weigh 50 mg Co@NC-700 catalyst, 100 mg bagasse lignin, 9 mL isopropanol and 1 mL formic acid, mix and place in a reactor, and seal the reactor. Replace the air in the reactor with argon for 5 times, and then fill it with 1 MPa argon. Connect the thermocouple. At a speed of 600 rpm, heat the reactor at 5 °C min. -1 Heat to 230°C at a rate of 1000 ℃ and hold for 4 h.
[0087] In this example, the lignin conversion rate was 83.3%, the total yield of monophenol products was 13.6 wt.%, the yield of 4-ethylphenol was 2.9 wt.%, and the selectivity was 21.3%.
[0088] Example 9: Preparation of monophenolic compounds by transfer hydrogenolysis of bagasse lignin catalyzed by Co@NC-500
[0089] The difference between this embodiment and embodiment 5 is that:
[0090] Weigh 75 mg Co@NC-500 catalyst, 100 mg bagasse lignin, 9 mL isopropanol and 1 mL formic acid, mix and place in a reactor, and seal the reactor. Replace the air in the reactor with argon for 5 times, and then fill it with 1 MPa argon. Connect the thermocouple. At a speed of 600 rpm, heat the reactor at 5 °C min. -1 Heat to 230°C at a rate of 1000 ℃ and hold for 4 h.
[0091] In this example, the lignin conversion rate was 88.6%, the total yield of monophenol products was 17.5 wt.%, the yield of 4-ethylphenol was 5.4 wt.%, and the selectivity was 30.9%.
[0092] Example 10: Preparation of monophenolic compounds by transfer hydrogenolysis of bagasse lignin catalyzed by Co@NC-500
[0093] The difference between this embodiment and embodiment 5 is that:
[0094] Weigh 100 mg Co@NC-500 catalyst, 100 mg bagasse lignin, 9 mL isopropanol and 1 mL formic acid, mix and place in a reactor, and seal the reactor. Replace the air in the reactor with argon for 5 times, and then fill it with 1 MPa argon. Connect the thermocouple. At a speed of 600 rpm, heat the reactor at 5 °C min. -1 Heat to 230°C at a rate of 1000 ℃ and hold for 4 h.
[0095] In this example, the lignin conversion rate was 89.1%, the total yield of monophenol products was 15.9 wt.%, the yield of 4-ethylphenol was 5.3 wt.%, and the selectivity was 33.3%.
[0096] Example 11: Preparation of monophenolic compounds by transfer hydrogenolysis of bagasse lignin catalyzed by Co@NC-500
[0097] The difference between this embodiment and embodiment 5 is that:
[0098] Weigh 125 mg Co@NC-500 catalyst, 100 mg bagasse lignin, 9 mL isopropanol and 1 mL formic acid, mix and place in a reactor, and seal the reactor. Replace the air in the reactor with argon for 5 times, and then fill it with 1 MPa argon. Connect the thermocouple. At a speed of 600 rpm, heat the reactor at 5 °C min. -1 Heat to 230°C at a rate of 1000 ℃ and hold for 4 h.
[0099] In this example, the lignin conversion rate was 90.2%, the total yield of monophenol products was 15.9 wt.%, the yield of 4-ethylphenol was 5.2 wt.%, and the selectivity was 32.7%.
[0100] Example 12: Preparation of monophenolic compounds by transfer hydrogenolysis of bagasse lignin catalyzed by Co@NC-500
[0101] The difference between this embodiment and embodiment 5 is that:
[0102] Weigh 150 mg Co@NC-500 catalyst, 100 mg bagasse lignin, 9 mL isopropanol and 1 mL formic acid, mix and place in a reactor, and seal the reactor. Replace the air in the reactor with argon for 5 times, and then fill it with 1 MPa argon. Connect the thermocouple. At a speed of 600 rpm, heat the reactor at 5 °C min. -1 Heat to 230°C at a rate of 1000 ℃ and hold for 4 h.
[0103] In this example, the lignin conversion rate was 90.1%, the total yield of monophenol products was 15.0 wt.%, the yield of 4-ethylphenol was 5.2 wt.%, and the selectivity was 34.7%.
[0104] Example 13: Preparation of monophenolic compounds by transfer hydrogenolysis of bagasse lignin catalyzed by Co@NC-500
[0105] The difference between this embodiment and embodiment 5 is that:
[0106] Weigh 50 mg Co@NC-500 catalyst, 100 mg bagasse lignin, 9 mL isopropanol and 1 mL formic acid, mix and place in a reactor, and seal the reactor. Replace the air in the reactor with argon for 5 times, and then fill it with 1 MPa argon. Connect the thermocouple. At a speed of 600 rpm, heat the reactor at 5 °C min. -1 Heat to 220°C at a rate of 100 °C and hold for 4 h.
[0107] In this example, the lignin conversion rate was 75.8%, the total yield of monophenol products was 15.4 wt.%, the yield of 4-ethylphenol was 4.5 wt.%, and the selectivity was 29.2%.
[0108] Example 14: Preparation of monophenolic compounds by transfer hydrogenolysis of bagasse lignin catalyzed by Co@NC-500
[0109] The difference between this embodiment and embodiment 5 is that:
[0110] Weigh 50 mg Co@NC-500 catalyst, 100 mg bagasse lignin, 9 mL isopropanol and 1 mL formic acid, mix and place in a reactor, and seal the reactor. Replace the air in the reactor with argon for 5 times, and then fill it with 1 MPa argon. Connect the thermocouple. At a speed of 600 rpm, heat the reactor at 5 °C min. -1 Heat to 240°C at a rate of 100 °C and hold for 4 h.
[0111] In this example, the lignin conversion rate was 89.4%, the total yield of monophenol products was 17.3 wt.%, the yield of 4-ethylphenol was 5.5 wt.%, and the selectivity was 31.8%.
[0112] Example 15: Preparation of monophenolic compounds by transfer hydrogenolysis of bagasse lignin catalyzed by Co@NC-500
[0113] The difference between this embodiment and embodiment 5 is that:
[0114] Weigh 50 mg Co@NC-500 catalyst, 100 mg bagasse lignin, 9 mL isopropanol and 1 mL formic acid, mix and place in a reactor, and seal the reactor. Replace the air in the reactor with argon for 5 times, and then fill it with 1 MPa argon. Connect the thermocouple. At a speed of 600 rpm, heat the reactor at 5 °C min. -1 Heat to 250°C at a rate of 100 °C and hold for 4 h.
[0115] In this example, the lignin conversion rate was 90.1%, the total yield of monophenol products was 16.1 wt.%, the yield of 4-ethylphenol was 4.9 wt.%, and the selectivity was 30.4%.
[0116] Example 16: Preparation of monophenolic compounds by transfer hydrogenolysis of bagasse lignin catalyzed by Co@NC-500
[0117] The difference between this embodiment and embodiment 5 is that:
[0118] Weigh 50 mg Co@NC-500 catalyst, 100 mg bagasse lignin, 9 mL isopropanol and 1 mL formic acid, mix and place in a reactor, and seal the reactor. Replace the air in the reactor with argon for 5 times, and then fill it with 1 MPa argon. Connect the thermocouple. At a speed of 600 rpm, heat the reactor at 5 °C min. -1 Heat to 230°C at a rate of 1.5 and hold for 2 h.
[0119] In this example, the lignin conversion rate was 79.0%, the total yield of monophenol products was 13.6 wt.%, the yield of 4-ethylphenol was 4.6 wt.%, and the selectivity was 33.8%.
[0120] Example 17: Preparation of monophenolic compounds by transfer hydrogenolysis of bagasse lignin catalyzed by Co@NC-500
[0121] The difference between this embodiment and embodiment 5 is that:
[0122] Weigh 50 mg Co@NC-500 catalyst, 100 mg bagasse lignin, 9 mL isopropanol and 1 mL formic acid, mix and place in a reactor, and seal the reactor. Replace the air in the reactor with argon for 5 times, and then fill it with 1 MPa argon. Connect the thermocouple. At a speed of 600 rpm, heat the reactor at 5 °C min. -1 Heat to 230°C at a rate of 1000 ℃ and hold for 6 h.
[0123] In this example, the lignin conversion rate was 87.4%, the total yield of monophenol products was 15.8 wt.%, the yield of 4-ethylphenol was 4.9 wt.%, and the selectivity was 31.0%.
[0124] Example 18: Preparation of monophenolic compounds by transfer hydrogenolysis of bagasse lignin catalyzed by Co@NC-500
[0125] The difference between this embodiment and embodiment 5 is that:
[0126] Weigh 75 mg of Co@NC-500 catalyst, 100 mg of bagasse lignin, 9 mL of isopropanol, and 1 mL of formic acid into a reactor and seal the reactor. Replace the air in the reactor with argon five times and then fill it with 1 MPa of argon. Connect the thermocouple. At a speed of 600 rpm, heat the reactor at 5 °C min. -1 Heat to 240°C at a rate of 100 °C and hold for 4 h.
[0127] In this example, the lignin conversion rate was 90.1%, the total yield of monophenol products was 17.7 wt.%, the yield of 4-ethylphenol was 6.1 wt.%, and the selectivity was 34.5%.
[0128] Example 19: Preparation of monophenolic compounds by transfer hydrogenolysis of bamboo lignin catalyzed by Co@NC-500
[0129] (1) Extraction of lignin: Mechanically crush and sieve the bamboo, and seal the bamboo powder of 80-120 mesh for later use. The ratio of ethanol / water in the extract is 4:1 (3200mL anhydrous ethanol, 800mL deionized water, 24g concentrated H2SO4). Place 10g of bamboo powder and 100mL of the extract in a hydrothermal reactor and heat at 100℃ for 4h. After the reaction is completed, cool naturally to room temperature. Filter, take the liquid phase, add 500mL deionized water, and let it stand to allow lignin to precipitate. Filter again, take the solid phase, vacuum dry overnight, grind and store in the dark. The resulting lignin is organic soluble bamboo lignin.
[0130] (2) Catalytic lignin hydrogenolysis: The catalytic lignin hydrogenolysis reaction was carried out in a high-pressure reactor. Weigh 50 mg of Co@NC-500 catalyst, 100 mg of bamboo lignin, 9 mL of isopropanol and 1 mL of formic acid into a reactor and seal the reactor. After replacing the air in the reactor with argon five times, fill it with 1 MPa of argon. Connect the thermocouple. At a speed of 600 rpm, heat the reactor at 5 °C min. -1 Heat to 230°C at a rate of 1000 ℃ and hold for 4 h.
[0131] In this example, the lignin conversion rate was 83.7%, the total yield of monophenol products was 10.3 wt.%, the yield of 4-ethylphenol was 1.7 wt.%, and the selectivity was 16.5%.
[0132] Example 20: Preparation of monophenolic compounds by transfer hydrogenolysis of poplar lignin catalyzed by Co@NC-500
[0133] (1) Extraction of lignin: The poplar wood is mechanically crushed and sieved, and the 80-120 mesh poplar wood powder is sealed and stored for later use. The ratio of ethanol / water in the extract is 4:1 (3200 mL of anhydrous ethanol, 800 mL of deionized water, 24 g of concentrated H2SO4). 10 g of poplar wood powder and 100 mL of the extract are placed in a hydrothermal reactor and heated at 100 °C for 4 h. After the reaction is completed, it is naturally cooled to room temperature. Filter, take the liquid phase, add 500 mL of deionized water, and let it stand to allow lignin to precipitate. Filter again, take the solid phase, vacuum dry overnight, grind and store in the dark. The resulting lignin is the organic soluble poplar wood lignin.
[0134] (2) Catalytic lignin hydrogenolysis: The catalytic lignin hydrogenolysis reaction was carried out in a high-pressure reactor. Weigh 50 mg of Co@NC-500 catalyst, 100 mg of poplar lignin, 9 mL of isopropanol and 1 mL of formic acid into a reactor and seal the reactor. After replacing the air in the reactor with argon five times, fill it with 1 MPa of argon. Connect the thermocouple. At a speed of 600 rpm, heat the reactor at 5 °C min. -1 Heat to 230°C at a rate of 1000 ℃ and hold for 4 h.
[0135] In this example, the lignin conversion rate was 85.2%, the total yield of monophenol products was 9.8 wt.%, the yield of 4-propylguaiacol was 2.2 wt.%, and the selectivity was 22.4%.
[0136] Example 21: Catalyst Recyclability
[0137] The Co@NC-500 catalyst was used for catalytic cycle test. The reuse process is as follows: after the reaction, the catalyst was separated by filtration and placed in an oven at 100-120°C for 12-24 hours without regeneration. The obtained catalyst solid was cycled according to the steps of Example 6. The test showed that the activity of the catalyst did not decrease significantly after being recycled for 5 times, the lignin conversion rate was 86.2%, the volatile product yield was 16.8%, and the 4-ethylphenol product yield was 5.1%.
[0138] It can be seen from the above examples that the cobalt-based nitrogen-carbon composite material catalytic system of the present invention cooperates with an organic hydrogen-donating solvent to realize the catalytic transfer hydrogenolysis of lignin to prepare monophenol products without the addition of external hydrogen. Under the conditions of 0.5-3MPa inert gas atmosphere, reaction temperature of 210-250°C, and reaction time of 2-6h, the conversion rate of lignin reaches 74.4-91.3%, and the total yield of monophenol products reaches 7.8-17.7%, among which the p-hydroxyphenyl products can reach 4.2-9.0%, and the selectivity is 38.4-50.8%. 4-Ethylphenol has a wide range of applications in the fields of food additives, cosmetics, and medicine; 4-propylguaiacol is widely used in flavored tobacco and daily chemical flavors; p-Hydroxyphenylpropionic acid and 4-propyl syringol are high value-added chemicals, which are widely used in the production of food additives and pharmaceutical intermediates. Therefore, the high selectivity of such products can improve the economy and overall utilization value of lignin.
[0139] Compared with the boron nitride-supported ruthenium catalyst invented in Chinese invention patent application CN202410599907.8, the transition metal-based catalyst used in the present invention can effectively depolymerize actual lignin and reduce dependence on rare metal resources, thereby improving the economy and sustainability in industrial applications, and giving the real lignin depolymerization process a higher practical application value and significance; compared with the RuNiZn / Nb2O5 catalyst invented in Chinese invention patent application CN202311659296.3, the catalyst of the present invention achieves efficient depolymerization of lignin without relying on external hydrogen supply, and the catalytic system is greener and safer. At the same time, it reduces the requirements for reaction conditions and can efficiently depolymerize lignin under milder reaction conditions; compared with the nickel-based alkaline carrier catalyst invented in Chinese invention patent application CN202410215194.0, the catalyst of the present invention has strong stability and no significant decrease in activity after 5 cycles.
[0140] The implementation methods of the present invention are not limited to the above-mentioned embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.
Claims
1. A method for preparing phenolic chemicals by catalyzing lignin transfer hydrogenolysis using a cobalt-based nitrogen-carbon composite material, characterized in that: The method uses organic soluble lignin as raw material, cobalt-based nitrogen-carbon composite material as catalyst, organic small molecule alcohol and formic acid as mixed solvent and hydrogen supply reagent, reacts at 210-250° C. for 2-6 hours in an inert gas atmosphere of 0.5-3 MPa, and catalyzes the depolymerization of lignin to obtain a monophenol product mainly composed of 4-ethylphenol; the cobalt-based nitrogen-carbon composite material is obtained by heat treating a Co-NDC precursor at 400-700° C. in a reducing atmosphere; the Co-NDC precursor is obtained by refluxing cobalt nitrate hexahydrate, 2,6-naphthalene dicarboxylic acid and 1,10-phenanthroline in a mixed solution at 100-120° C., filtering, drying and grinding; the mixed solution consists of N,N-dimethylformamide, water and an alkaline regulator.
2. The method for preparing phenolic chemicals by catalyzing transfer hydrogenolysis of lignin by a cobalt-based nitrogen-carbon composite material according to claim 1, characterized in that: The molar ratio of the cobalt nitrate hexahydrate, 2,6-naphthalene dicarboxylic acid and 1,10-phenanthroline is (0.5-1.5):1:1; the mass ratio of the cobalt nitrate hexahydrate and the mixed solution is 1:(90-110); the volume ratio of N,N-dimethylformamide, water and alkaline regulator in the mixed solution is 20:1:(1.5-2.5).
3. The method for preparing phenolic chemicals by catalyzing lignin transfer hydrogenolysis using a cobalt-based nitrogen-carbon composite material according to claim 2, characterized in that: The reflux time at 100-120° C. is 24-32 hours; the alkaline regulator is one or more of formamide, diethylamine, N,N-tetramethylhexanediamine, and isopropanolamine.
4. The method for preparing phenolic chemicals by catalyzing transfer hydrogenolysis of lignin by a cobalt-based nitrogen-carbon composite material according to claim 1, characterized in that: The mass ratio of the organic soluble lignin to the cobalt-based nitrogen-carbon composite material is 1:(0.5-1.5); the mass ratio of the organic small molecule alcohol to formic acid in the mixed solvent is 9:(0.5-1.5); and the mass ratio of the organic soluble lignin to the mixed solvent is 1:(7-9).
5. The method for preparing phenolic chemicals by catalyzing transfer hydrogenolysis of lignin by a cobalt-based nitrogen-carbon composite material according to claim 1, characterized in that: The reducing atmosphere is a carbon monoxide / nitrogen mixed gas; the inert gas atmosphere is any one or more of nitrogen, argon and helium; and the catalytic lignin depolymerization is carried out in an intermittent high-pressure reactor.
6. The method for preparing phenolic chemicals by catalyzing transfer hydrogenolysis of lignin by a cobalt-based nitrogen-carbon composite material according to claim 1, characterized in that: The heat treatment time is 6 to 7 hours; the organic small molecule alcohol is any one or more of methanol, ethanol, n-propanol, isopropanol and formic acid.
7. The method for preparing phenolic chemicals by catalyzing transfer hydrogenolysis of lignin by a cobalt-based nitrogen-carbon composite material according to claim 1, characterized in that: The organosoluble lignin is obtained by taking biomass as substrate and extracting it through an organic solvent method.
8. The method for preparing phenolic chemicals by transfer hydrogenolysis of lignin catalyzed by a cobalt-based nitrogen-carbon composite material according to claim 7, characterized in that: The organic solvent extraction method is to react the biomass with a mixed extract of 1,4-dioxane / dilute sulfuric acid at 90-150° C. for 2-8 hours, filter the filtrate, add deionized water to the filtrate to precipitate lignin, let it stand for 12-24 hours and then filter, dry and grind the filter cake to obtain the organic soluble lignin.
9. The method for preparing phenolic chemicals by transfer hydrogenolysis of lignin catalyzed by a cobalt-based nitrogen-carbon composite material according to claim 8, characterized in that: The biomass is any one or more of bagasse, corn stalks, corn cobs, bamboo, poplar, birch and pine, which is obtained by mechanical crushing and screening out 80-120 meshes; in the 1,4-dioxane / dilute sulfuric acid extract, the volume ratio of 1,4-dioxane to dilute sulfuric acid is (6-7):1; the amount of ethanol / water mixed extract per gram of biomass raw material is 10-20mL; the dilute sulfuric acid is prepared by adding 9-12g of deionized water to concentrated sulfuric acid with a mass concentration of 95-98% per gram.
10. The method for preparing phenolic chemicals by transfer hydrogenolysis of lignin catalyzed by a cobalt-based nitrogen-carbon composite material according to claim 1, characterized in that: The monophenols include 4-ethylphenol, 4-propylphenol, p-hydroxyphenylpropionic acid, 4-ethylguaiacol, 4-propylguaiacol, 4-propyleneguaiacol, 2,6-dimethoxyphenol, 2,6-dimethoxy-4-propylphenol, and 2,6-dimethoxy-4-propylenephenol.
Citation Information
Patent Citations
A method for catalytic depolymerization of lignin into phenolic compounds using RuNiZn / Nb2O5 catalyst.
CN117645530B
Method for preparing C2-phenol monomer by hydrogenolysis of lignin with nickel-based alkaline carrier catalyst
CN118122361A
Boron nitride supported ruthenium catalyst for efficient hydrogenolysis of aromatic ether
CN118341468A
Method for preparing 4-ethyl phenol by selective lignin hydrogenolysis
CN107235829A
Method for preparing 4-ethylphenol by depolymerizing lignin based on liquid phase reforming system
CN112608219A
Cited By
Preparation method of oxidized lignin based on lignin priority strategy
CN119978428A